International conference Fluid Power 2021: Conference Proceedings - Marina Bajić; Lovrec, Darko; Tič, Vito (2021)
The International Fluid Power Conference is a two-day event, intended for all those professionally involved with hydraulic or pneumatic power devices and for all those, wishing to be informed about the ‘state of the art’, new discoveries and innovations within the field of hydraulics and pneumatics. The gathering of experts at this conference in Maribor has been a tradition since 1995, and is organised by the Faculty of Mechanical Engineering at the University of Maribor, in Slovenia. Fluid Power conferences are organised every second year and cover those principal technical events within the field of fluid power technologies in Slovenia, and throughout this region of Europe. This year's conference is taking place on the 16th and 17th September in Maribor. The main focus of this year's contributions is on the integration of information systems in the field of fluid technology.
Keywords: international conference; fluid power; science and profession; inovations; achievements